Levantamento e análise do processo projetual de artefatos multimídia populares - aparelhagens - Soares, João Roberto dos Santos (2015)
The Aparelhagem is a popular multimedia artifact, originated from a very specific craft process of design, serving two main needs: physical-structural support to Aparelhagem’s Parties and communicate an aesthetic concept that will be explored from semiotic performances of a DJ and the public of the party itself. The survey mapped the design process of the Stereos, unspoken and cultural information with matching theories of Design, meeting aspirations of social integration of the knowledge. For that, the literature review aimed to understand the formation of the concepts of culture, identity and their reflections in contemporary times, as well as their influences in making design and be designer. Used as a method to ethnography and the systematic observation of the creation, as well as tools used for benchmarking methodologies considered more relevant in the field of design, with the aim of checking the range of the design in this activity. For data collection, a case study was conducted with three workshops, equipment manufacturers in order to extract and systematize the information project, where they revealed cultural aspects that can be incorporated into the traditional concept of design, since the culture of a society is rich in symbols and can be cumulative in its aesthetic and functional process. With that, the research presented here, was intended to create more consistent elements for ongoing project practices, contributing to the design of equipment, the design project through the systematization of information.